2022
DOI: 10.3390/pharmaceutics14122824
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a Fully Human Anti-MUC-16 Antibody and Evaluation as a PET Imaging Agent

Abstract: Antibodies that recognize cancer biomarkers, such as MUC16, can be used as vehicles to deliver contrast agents (imaging) or cytotoxic payloads (therapy) to the site of tumors. MUC16 is overexpressed in 80% of epithelial ovarian cancer (EOC) and 65% of pancreatic ductal adenocarcinomas (PDAC), where effective ‘theranostic’ probes are much needed. This work aims to develop fully human antibodies against MUC16 and evaluate them as potential immuno-PET imaging probes for detecting ovarian and pancreatic cancers. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Consistent with this, we performed live cell staining to find that the surface expression of MUC16 in SKOV3 cells was significantly lower, compared to OVCAR3 cells. These findings are consistent with previous studies and offer an explanation to the apparent discrepancy between the work of Zhao and colleagues and our current study [ 47 , 48 ]. Further confirmation of our hypothesis was provided by our experiments that showed that MSLN-CAR T cells could lyse SKOV3 cells that overexpressed MUC16.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this, we performed live cell staining to find that the surface expression of MUC16 in SKOV3 cells was significantly lower, compared to OVCAR3 cells. These findings are consistent with previous studies and offer an explanation to the apparent discrepancy between the work of Zhao and colleagues and our current study [ 47 , 48 ]. Further confirmation of our hypothesis was provided by our experiments that showed that MSLN-CAR T cells could lyse SKOV3 cells that overexpressed MUC16.…”
Section: Discussionsupporting
confidence: 93%
“…The binding affinity and specificity of N4MU01 were evaluated by flow cytometry using nectin-4 expressing breast cancer cells MDA-MB-468, MCF-7, 4T1. nectin-4 and nectin-4 negative MDA-MB-231 cells as described previously [21]. The detailed method is described in the supplementary section.…”
Section: Methodsmentioning
confidence: 99%
“…The internalization of N4MU01 was studied for 48 h using the Incucyte live-cell imaging system as described previously [21]. The detailed method is described in the supplementary method section.…”
Section: Methodsmentioning
confidence: 99%
“…confirmed the significant cytotoxicity of MUC16 ectodomain-specific bispecific single-chain variable fragments (BiTEDs) against ovarian cancer cells in vitro , effectively delaying tumor progression in vivo , especially when combined with anti-angiogenic treatment, showing potential for extending survival ( 147 ). Additionally, Babeker’s team’s investigation into the fully human monoclonal antibody M16Ab in ovarian cancer immune PET imaging revealed that the 89Zr-DFO-M16Ab conjugate specifically targets MUC16-positive tumor cells, underscoring the potential of fully human antibodies in diagnostic imaging and radiopharmaceutical development ( 148 ). Rao et al.…”
Section: Clinical Progress Of Immunotherapies Targeting Muc1 and Muc16mentioning
confidence: 99%